Axial length acquisition success rates and agreement of two swept-source optical biometers in eyes with dense cataracts - Orts-Vila, Paz; Tañá-Sanz, Santiago; Tello-Elordi, Cristina; Montés-Micó, Robert; Tañá-Rivero, Pedro (Frontiers in Medicine, 2024)
Background Swept-source optical coherence tomography–based (SS-OCT) biometers have been used in different clinical studies with the aim of assessing the accuracy of the technique, specifically in eyes with dense cataracts. Our objective is to evaluate the axial length acquisition success rates and agreement of two SS-OCT biometers when measuring axial length and biometric parameters in eyes with dense cataracts. Methods 46 eyes (46 patients) with dense cataracts (LOCS III grade ≥ 4) were measured 3 consecutive times using the Eyestar 900 and Argos SS-OCT biometers. Keratometry (K1, flat and K2, steep), central corneal thickness (CCT), white-to-white (WTW), anterior-chamber-depth (ACD), lens-thickness (LT), and axial length were measured using both biometers. The percentage acquisition success rate and a Bland–Altman analysis to determine the agreement between the biometers were calculated. Corrected and uncorrected distance visual acuity, subjective refraction, and axial length (to assess preoperative axial length accuracy) were measured 1-month post-cataract surgery. Results The mean LOCS III score was 4.37 ± 0.68. The acquisition success rates for both biometers was 100%. There were statistically significant differences between the two SS-OCT biometers for all parameters evaluated (p < 0.05). The mean differences for K1, K2, CCT, WTW, ACD, LT and axial length were 0.106 D, 0.128 D, −6.347 μm, −0.054 mm, 0.095 mm, 0.110 mm, and −0.036 mm, respectively. The mean pre- and post-surgery axial length difference was −0.036 mm for the Eyestar 900 and −0.020 mm for the Argos. This difference was ≤ 0.1 mm in 97.82% of eyes with the Eyestar 900 and in 100% of eyes with the Argos. Conclusion SS-OCT biometry successfully measures axial length in dense cataracts. The differences between biometers in some parameters may have a clinically significant impact but should be judged individually. The pre- and post-surgery axial length differences for each biometer can be considered clinically negligible and should not affect the IOL power calculation.